Clinical efficacy of mogamulizumab for relapsed/refractory aggressive adult T‐cell leukemia/lymphoma: A retrospective analysis. (16th September 2020) - Satake, Atsushi; Konishi, Akiko; Azuma, Yoshiko; Tsubokura, Yukie; Yoshimura, Hideaki; Hotta, Masaaki; Nakanishi, Takahisa; Fujita, Shinya; Nakaya, Aya; Ito, Tomoki; Ishii, Kazuyoshi; Nomura, Shosaku
Abstract: Objectives: Although phase 2 studies have confirmed the efficacy of mogamulizumab for adult T‐cell leukemia/lymphoma (ATL), real‐world data on its benefits are limited. We assessed the benefits of mogamulizumab for relapsed/refractory ATL in clinical practice. Methods: We retrospectively analyzed patients with acute‐ and lymphoma‐type ATL. Among 57 patients diagnosed with ATL between January 2008 and August 2018, 42 who received salvage therapy were eligible, including 24 who received mogamulizumab. Results: The overall response rate to mogamulizumab was 54.2%. Median survival time (MST) and 1‐year overall survival (OS) rate from mogamulizumab initiation were 7.7 months and 42.0%, respectively. Patients with acute‐type ATL showed longer MST (15.1 months) and higher 1‐year OS (63.6%). MST without skin rash was 5.0 months, and 1‐year OS was 34.3%; however, MST with skin rash was not reached and 1‐year OS was 66.7%. Among patients who received the salvage therapy, longer MST and higher 1‐year OS were observed with mogamulizumab than without mogamulizumab ( P = .078; 9.2 vs. 3.9 months; 47.9% vs. 17.6%, respectively). Mogamulizumab administration improved prognosis in patients with acute‐type ATL and skin rash. Conclusions: In clinical practice, mogamulizumab improved OS in patients with relapsed/refractory ATL, especially those with acute‐type ATL and skin rash.